GOVERNANCE-BASED SUSTAINABILITY RISK INTEGRATION AND FIRM VALUE: DOES OWNERSHIP STRUCTURE MATTER? - Alfistia Maradidya; Indah Kartika Sandhi (Universitas PGRI Semarang, 2026)
Corporate sustainability has become an essential element of corporate governance, requiring firms to integrate environmental, social, and governance (ESG) considerations into strategic decision-making and enterprise risk management. Although prior studies have widely examined ESG disclosure and sustainability reporting, limited attention has been given to how sustainability-related risks are embedded within governance and risk management processes. Evidence regarding the moderating role of ownership structure in this relationship also remains inconclusive, particularly in emerging markets. This study investigates the effect of Governance-Based Sustainability Risk Integration (GBSRI) on firm value and examines whether ownership structure moderates this relationship. A quantitative explanatory approach was employed using balanced panel data comprising 75 firm-year observations from 15 Indonesian listed companies operating in high-risk industries during 2020–2024. The GBSRI Index integrates the COSO ERM Framework, GRI Standards, and IFRS S1 and S2 into a governance-oriented framework with seven dimensions and 30 indicators. Using MRA with pooled OLS, the study finds that GBSRI has no significant effect on firm value, and ownership structure does not moderate this relationship. Nevertheless, the GBSRI Index contributes to sustainability accounting by offering a comprehensive framework for assessing sustainability risk integration into corporate governance and enterprise risk management, particularly in high-risk industries.